Cinética de liberação de clorexidina em nanocompósito de magnetita e quitosana - Mendes, Ana Paula Pais (2019)
Nanocomposites are used in several fields of knowledge, including nanomedicine. They are used as drug carriers because of their biocompatibility and biological activity, with possible antimicrobial activity. This study aimed to evaluate the effect of magnetic nanoparticle insertion on a chitosan polymer matrix as carriers of antimicrobial antibiotics. The chitosan suspension was prepared by solubilizing it in 2% acetic acid under constant magnetic stirring at room temperature for 24 hours. The colloidal suspension of magnetite (Fe3O4) was supplied by the company nChem, São Carlos (Brazil). The nanocomposites were prepared in a simple mixing process. Chlorhexidine was added to the nanocomposites under constant magnetic stirring at room temperature. The nanocomposites were obtained as expected and reproducibly. The magnetite nanoparticles were recovered by chitosan and the homogeneous incorporation of the drug into the polymer matrix. The data obtained in the drug release tests were analyzed at foiur different temperatures and it was concluded that the magnetite-chitosan system releases chlorhexidine during the first 2 hours until reaching 60% release by the method described by Krosmeyer-Peppas. After the 2 hours of release, another model goes on to describe the release, the Higuchi model.